Effects of microwave irradiation on the characteristics and mesophilic anaerobic digestion of sequencing batch reactor sludge - Thibault, Gabriel (University of Ottawa (Canada), 2006)
Wastewater treatment generates large quantities of sewage sludge whose disposal is expensive. Mainly because anaerobic digestion produces methane, which can be beneficially used as an energy source, this process has become the most popular means of stabilizing sewage sludge prior to spreading on agricultural land or disposal to landfills. Several pretreatment technologies have recently been developed to render sludge more degradable during anaerobic digestion. The purpose of this study is to investigate whether microwave irradiation can enhance the anaerobic degradability of aerobic sequencing batch reactor sludge. Relationships relating microwave irradiation duration, microwave intensity, sludge concentration and the temperature reached by the sludge were developed. Sludge concentration in the 1.2-4.3% total solids range was found not to impact the temperature reached by the sludge. Three techniques were used to assess the impact of microwave irradiation on the size of the particles: visual analysis of sludge settling, microscopic analysis and particle size distribution analysis. (Abstract shortened by UMI.)
Keywords: Environmental Sciences.; Engineering, Environmental.